Influencing gambling attitudes : what the media tells youths? - Luo, Yuzheng (2014)
In this article, an overview of existing literature regarding influences of films and advertisements on youth gambling is provided. Next, major theories explaining how media impacts gambling among youths, are outlined. With that as a foundation, a review of specific tools and techniques used in films and advertisements, which encourage pro-gambling attitudes and behaviour in youths, is addressed. Lastly, discussed techniques will be applied to anti-gambling media content to propose improvements to consistency and effectiveness in aiding the prevention of gambling among youths.